The Feasibility of Enhanced Geothermal Systems (EGS) for District Heating and Hot Water Production in Holmavik, Iceland - Crompton, Adam, 1992- (2016)
Some communities in Iceland which are not located near a high temperature geothermal areas have to pay a premium for heating. This paper will explore a method that involves creating an enhanced geothermal system (EGS) for district heating, this method has been used in places with much lower geothermal gradients than in Iceland. An EGS is typically used in areas where little natural fluid exists and the rock has low permeability, this rock has to be fractured to allow a medium to permeate through and extract heat. This paper aims to determine if using an EGS would be a feasible idea for district heating and hot water (DHHW) production for a small town of 341 people in Holmavik, Iceland. Data was gathered regarding; the geothermal resource, reservoir model, equipment, capital costs and economic aspects of an EGS plant; these values where used to make two comparative simulations for towns of different sizes. From this simulation data was obtained for production fluid temperature, total heat production and reservoir depletion over the 25 years the project would run; the breakeven price per kWh was also determined. The results from the first simulation are based on data from heating and hot water demand obtained from the Westfjords Power Company, for Holmavik. Whereas, the second simulation projects the heating demand of Holmavik onto a town 7.5 times the size of it, in this case Isafjordur. Both simulations are able to sufficiently provide enough heat for DHHW; the depletion of the reservoir for Holmavik is only 3%, for Isafjordur it is 23%. The breakeven cost over the life of the project are 0.15 ($/kWh) and 0.0793 ($/kWh) for Holmavik and Isafjordur respectively. For such a small community like Holmavik it is not feasible to use an EGS for DHHW due to very high initial investment. For a larger community like Isafjordur using EGS for DHHW is still not feasible since the breakeven price is still greater than what residents are currently paying for electricity.